Degradation of anionic azo dyes in aqueous solution using a continuous flow photocatalytic packed-bed reactor: Influence of water matrix and toxicity evaluation. Issue 6 (December 2020) - Vaiano, Vincenzo; Sacco, Olga; Libralato, Giovanni; Lofrano, Giusy; Siciliano, Antonietta; Carraturo, Federica; Guida, Marco; Carotenuto, Maurizio
Graphical abstract: Highlights: Textile dyes (EBT and MeO) can represent a serious environmental threat. EBT and MeO were treated by a continuous flow UV-LEDs TiO2 packed-bed reactor. A single photocatalytic step achieved the total decolourization and toxicity removal of EBT. Only combining photocatalysis and activated carbon treatments MeO and its toxictywere removed. Abstract: A continuous flow photocatalytic packed-bed reactor irradiated by UV-LEDs was employed for the degradation of two toxic anionic azo dyes: Eriochrome Black-T (EBT) and Methyl Orange (MeO). Commercial anatase TiO2 in pellets form was used as packing material for the photoreactor. The experimental tests were carried out using both distilled and tap water as aqueous matrix for the two selected dyes. The influence of the liquid flow rate on the performances of the photocatalytic packed-bed reactor was investigated in the range 0.5–2.1 mL/min. Photocatalytic results showed that, under UV light, the system allows to achieve steady-state dyes concentration values without deactivation phenomena in 510 min irradiation time. Using distilled water, the highest efficiency of the process (EBT and MeO decolorization of about 100 % and 90 %, respectively) was observed with a liquid flow rate of 0.5 mL/min (contact time =6.6 min). In the presence of tap water and using the same contact time, the EBT decolourization was still total whereas MeO degradation was lower and equal to 70 %. For this reason, the photocatalytic reactor was followed by an adsorption unit based on the use of activated carbon. With such configuration, the complete MeO decolourization was achieved. The total removal of toxicity for EBT was achieved with just one packed-bed reactor being the toxicity of potential by-products not relevant. In the case of MeO, the full toxicity removal was obtained only after powdered activated carbon filtration.